ANALISIS LINGKUNGAN INTERNAL DAN EKSTERNAL DALAM PENCAPAIAN TUJUAN PERUSAHAAN (Studi Kasus di PT. Perkebunan Nusantara VII Lampung) - Devi Yulianti (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2014)
The research about the analysis of internal and external environments was done in PT. Perkebunan Nusantara VII (Persero) which is one of public enterprises, focusing its business in plantations in Lampung, Indonesia. The aims of the research are to describe and analyze the internal and external environments towards the achievement of corporation’s goals. The research used a qualitative approach with descriptive type. Meanwhile the data collection used the documentation and observation. The data analysis technique used some kind of procedures such as the reduction data, the display of data and the conclusion. The conclusions from this research were shown that based on the analysis technique using internal and external evaluation factors matrix, the corporation was still unable to cover its weakness and still unable to use the opportunity to overcome the threats. Based on that conclusion, the writer has suggested some advices such as the corporation should work together with the third party to create the survey in order to examine the internal and external factors or to maximize the role of research and development division of its own.